Improving regulatory efficiency for biotechnology products - Koch, Muffy; Pence, Matthew G.; DeMond, Jaylee; Rudgers, Gary (Frontiers in Bioengineering and Biotechnology, 2024)
Small procedural changes in how regulatory agencies implement biotech policies can make significant differences in improving regulatory efficiency. This paper discusses how science based, crop specific guidance documents can improve dossier content and the review and approval of biotech varieties. In addition, we describe how the adoption of established risk assessment methodology and applying policy-linked decision making at the agency level can boost both efficiency and developer, public and government confidence in agency decision making and in biotech crops.